2014
DOI: 10.2141/jpsa.0130237
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphism in the <i>LDHA </i>Gene as a Potential Marker for the Racing Performance of Pigeons

Abstract: The objective of the present study was to investigate the relationship between the g.2582481G>A, g.2583935G >A and g.2584057C>T single nucleotide polymorphisms (SNPs) within the lactate dehydrogenase A gene (LDHA) coding for lactate dehydrogenase isoform A and the racing performance of homing pigeons. As a measure of racing performance, we used the mean values of ace points won by individual birds during the whole season. The estimated heritability of the racing performance of pigeons was relatively low (h 2 =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 9 publications
3
26
0
Order By: Relevance
“…The CTCT genotype was linked to the highest ace points mean and the CCCC genotype to the lowest mean. Possible dependence of pigeon racing ability on genetic variation has been reported before and, also, association of the LDHA polymorphism with performance of pigeons in races at short distances has been indicated recently . In sum, our data suggest that dopamine receptor D4 variants could play an important role in pigeon performance during short races.…”
Section: Commentssupporting
confidence: 81%
See 1 more Smart Citation
“…The CTCT genotype was linked to the highest ace points mean and the CCCC genotype to the lowest mean. Possible dependence of pigeon racing ability on genetic variation has been reported before and, also, association of the LDHA polymorphism with performance of pigeons in races at short distances has been indicated recently . In sum, our data suggest that dopamine receptor D4 variants could play an important role in pigeon performance during short races.…”
Section: Commentssupporting
confidence: 81%
“…Ace points acquired by pigeons in races were calculated as described before on the basis of 1380 race records from eight short (<400 km) and six long (>500 km) races. Associations between ace points and SNPs were analysed with a mixed model using the lmekin package for r software.…”
Section: Association Analysismentioning
confidence: 99%
“…The breeding of suitable racing pigeons is lucrative, with a price of $328,000 for an individual in 2012 [ 5 ]. The distances of major races in Japan range from 100 km to 1000 km, while international races, such as Diamond Elite and Golden Island One-loft in China, are 300 miles and 310 miles, respectively [ 6 ]. Thus, racing pigeons are under intensive selection for improving of speed, endurance during long flights [ 7 ], along with general survivability and homing ability.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic markers have been used to predict racing performance in humans [ 13 ], horses [ 14 ], dogs [ 15 ], and pigeons [ 6 , 16 , 17 ]. These studies have indicated that lactate dehydrogenase isoform A, encoded by the lactate dehydrogenase A gene ( LDHA ), is critical to the aerobic/anaerobic metabolism of different tissues and thus to overall physiological performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation